Review Of The Diversity Of Crab (Ocypodidae) In Indonesia Which Can Be Used As A Bioindicator Of Environmental Pollution - Kaprian Alsyah Kurnia Kurnia; Rijal Satria (Jurnal Serambi Biologi, 2023)
Indonesia is a country known as a mega-biodiversity country, also known as an archipelagic country, which has a long coastline of 95,181 km, the second longest in the world after Canada. The area of Indonesian sea waters reaches 5.8 million km2, or 71% of the total territory of Indonesia. Thus, Indonesia is a country that has an abundant wealth of biological natural resources, one of which is marine biota from the crustacean group, namely crabs. One of the crab families is Ocypodidae. The crabs of the Ocypodidae family have an important role in the ecosystem. This study aims to see the potential of Ocypodidae crabs as bioindicators based on the results of previous studies. The method used in this research is descriptive research by conducting online surveys through articles from previous studies and from the Crab Database web. A total of four genera of crabs from the Ocypodidae family are found in Indonesia, namely: Austruca (three species), Gelasimus (two species), Ocypode (three species), and Tubuca (three species). We assume that crabs from the Ocypodidae family have the potential to be used as bioindicators of existing environmental pollution.